Oxidative nanopatterning of titanium surfaces promotes production and extracellular accumulation of osteopontin - Bueno,Renan de Barros e Lima (2011)
The bone-biomaterial interface has been characterized by layers of afibrillar extracellular matrix (ECM) enriched in non collagenous proteins, including osteopontin (OPN), a multifunctional protein that in bone controls cell adhesion and ECM mineralization. Physical and chemical aspects of biomaterial surfaces have been demonstrated to affect cell-ECM-substrate interactions. The present paper described the ability of oxidative nanopatterning of titanium (Ti) surfaces to control extracellular OPN deposition in vitro. Ti discs were chemically treated by a mixture of H2SO4/H2O2 for either 30 min [Nano(30') Ti] or 4 h [Nano(4h) Ti]. Non-etched Ti discs were used as control. Primary osteogenic cells derived from newborn rat calvarial bone were plated on control and etched Ti and grown under osteogenic conditions up to 7 days. High resolution scanning electron microscopy revealed that treated Ti discs exhibited a nanoporous surface and that areas of larger nanopits were noticed only for Nano(4h) Ti. Large extracellular OPN accumulation were detectable only for Nano(4h) Ti, which was associated with OPN-positive cells with typical aspects of migrating cells. At day 3, quantitative results in terms of areas of OPN labeling were as follows: Nano(4h) Ti > Nano(30') Ti > Control Ti. In conclusion, chemically nanostructured Ti surfaces may support the enhancement of endogenous extracellular OPN deposition by osteogenic cells in vitro depending on the etching time, a finding that should be taken into consideration in strategies to biofunctionalize implant surfaces with molecules with cell adhesion capacity.